Disidentification: The long-term effects of offensive-discriminatory advertising - Friedmann, E.; Solodoha, E.; Loureiro, S. M. C.; Avieli, L. (Psychology and Marketing, 2025)
This study explores the long-term consumer responses following exposure to offensive-discriminatory advertising (ad) among members of discriminated groups. It aims to understand the dynamic consumer effect of such ads, particularly for those who feel their group is highly discriminated against and who wish to disidentify from their group. Three longitudinal experiments were conducted: race-offensive (n = 347) and two gender-offensive studies (n = 221, and n = 72). Offensive-discriminatory and non-offensive-discriminatory ads were presented to women and Black participants, and consumer responses were measured at two-time points. Individuals feeling highly discriminated against who tended to distance themselves from their group showed more compensatory brand responses (brand purchase intentions, actual brand choice, and Frontal Alpha Asymmetry score as a measure of approach avoidance tendency) over time than those feeling less group discrimination. This study adds to the literature by showing the temporal dynamics of disidentification triggered in responses to offensive-discriminatory ads. It highlights the role of time in consumer behavior and quantifies long-term responses among different segments. It also extends the disidentification theory from workplace settings to ad contexts. These studies reveal the long-term effects of offensive-discriminatory ads on specific consumer segments and the complex dynamics between consumers, brands, and social identities. It emphasizes the need for ethical regulation of such ads, which provoke compensatory responses from stigmatized groups.